Numerical Fit to the Ashkin Experiment for the 4-Different Formulas of Volume Momentum Proposed by Abraham, Minkowski, Peierls, and Klima-Petrzilka - Sidikrubadi Pramudito; Yuliati Herbani (Indonesian Journal of Physics, 2002)
The momentum flux density of electromagnetic radiation in dielectric media (Abraham-Minkowski problem) has not yet been solved while this question seems to be settled for collisionless fully ionized plasma. Therefore, the experiments of Ashkin are analyzed for a numerical evaluation of the total momentum transferred by laser beam to the sphere suspended in a fluid using four competing formulas for volume momentum, given by Abraham, Minkowski, Peierls, and Klima-Petrzilka. It turns out that at least for this condition of high frequency radiation the Minkowski’s formula as predicted by Gordon arrives at the best fit with experiments and no term of Claussius-Mosotti media are involved at this process of radiation forces.